67.5k views
0 votes
If h(x) = 5 + x and k(x)=
, which expression is equivalent to (k•h)(x)

User Lbrutti
by
5.7k points

2 Answers

0 votes

Answer:

1/(5+x) or also know as B if ur doing edge

Explanation:

I just did it

User Tatjana Heuser
by
6.0k points
2 votes

If h(x) = 5x and k(x) = 1/x

Then (k o h) (x) = k ( h(x) ) = k(5x) = 1/(5x)

2) If h(x) = 5 + x and k (x) = 1/x

Then (k o h)(x) =k ( h(x) ) = k (5+x) = 1 / [5 + x]

-Hope this helps-

Please mark brailiest

User Shrinivas Shukla
by
5.8k points